2021
DOI: 10.1080/17461391.2021.2001575
|View full text |Cite
|
Sign up to set email alerts
|

Acute L‐glutamine supplementation does not improve gastrointestinal permeability, injury or microbial translocation in response to exhaustive high intensity exertional‐heat stress

Abstract: Purpose: Exertional-heat stress adversely distrupts (GI) barrier integrity and, through subsequent microbial translocation (MT), can result in potentially fatal exertional-heat stroke. Acute glutamine (GLN) supplementation is a potential nutritional countermeasure, although the practical value of current supplementation regimens is questionable. Method: Ten males completed two high-intensity exertional-heat stress tests (EHST) involving running in the heat (40°C and 40% relative humidity) at lactate threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Although there is substantial research exploring the impact of exercise stress on direct or indirect markers of bacterial endotoxin translocation [e.g., plasma lipopolysaccharides (LPS), LBP, sCD14, and/or EndoCAb concentration], research into exercise-associated whole bacterial luminal to systemic translocation (i.e., bacteremia) is scarce ( Costa et al, 2022 ). Some previous studies have attempted to detect whole bacteria presence in circulation (e.g., total 16S bacteria: Bacteroides ratio) in response to prolonged low intensity exercise (i.e., 80 min fixed-intensity treadmill walking- 6 km/h and 7% gradient) ( Ogden et al, 2020a ; Ogden et al, 2020b ), and higher intensity of shorter duration exercise (i.e., 60 min running at 70% V̇ O 2peak ) ( March et al, 2019 ; Ogden et al, 2022 ), with findings modest and inconsistent. Variability of bacterial translocation in response to these exercise bouts may be explained by the application of insufficient exertional stress among studies, a lack of control of confounding factors within experimental procedures, and/or the biomarker selected to represent whole bacterial translocation into systemic circulation (i.e., Bacteriodes /total bacterial DNA) ( Costa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is substantial research exploring the impact of exercise stress on direct or indirect markers of bacterial endotoxin translocation [e.g., plasma lipopolysaccharides (LPS), LBP, sCD14, and/or EndoCAb concentration], research into exercise-associated whole bacterial luminal to systemic translocation (i.e., bacteremia) is scarce ( Costa et al, 2022 ). Some previous studies have attempted to detect whole bacteria presence in circulation (e.g., total 16S bacteria: Bacteroides ratio) in response to prolonged low intensity exercise (i.e., 80 min fixed-intensity treadmill walking- 6 km/h and 7% gradient) ( Ogden et al, 2020a ; Ogden et al, 2020b ), and higher intensity of shorter duration exercise (i.e., 60 min running at 70% V̇ O 2peak ) ( March et al, 2019 ; Ogden et al, 2022 ), with findings modest and inconsistent. Variability of bacterial translocation in response to these exercise bouts may be explained by the application of insufficient exertional stress among studies, a lack of control of confounding factors within experimental procedures, and/or the biomarker selected to represent whole bacterial translocation into systemic circulation (i.e., Bacteriodes /total bacterial DNA) ( Costa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…After HAT, biomarkers of organ injury and inflammatory factors showed significant changes, including alpha-tumor necrosis factor (TNF-α), interleukin-6 (IL-6), IL-10, IL-18, intestinal fatty acid-binding protein (I-FABP), neutrophil gelatinase-associated lipocalin (NGAL), heat shock protein 72 (HSP72), and kidney injury molecule-1 (KIM-1) (Dolci et al, 2015;Lee and Thake, 2017;Chapman et al, 2021;Osborne et al, 2021). The pathophysiology of HS is caused, at least in part, by a systemic inflammatory response induced by gastrointestinal microbe leakage into the bloodstream (Ogden et al, 2021). Cao et al demonstrated that a 28-day HAT improved the structure of the gut microbiome community and the fecal metabolome in rats, providing novel insights into improving the gut microbiome and its functions as a potential mechanism for HA's protective properties under heat stress (Cao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%